Metagenome data of bacterial diversity in pear (Pyrus communis L.) rhizospheres associated with Phytophthora infection and amino acid treatment - Antonios Zambounis (2020)
© 2019 The Authors The bacterial diversity in rhizosphere soil of pear trees (Pyrus communis L. cv. Krystalli) from an orchard at Thessaly region of Greece was characterized employing amplicon-based metagenomics analysis. Pathogenic filamentous oomycetes of the genus Phytophthora comprises more than 150 recognized species and cause highly destructive soil-borne diseases in deciduous trees crops worldwide. Moreover, the treatment of soil microbiota with amino acids is an alternative strategy to achieve desirable effects even against phytopathogenic oomycetes. In our study, samples from rhizosphere soil were collected either from naturally Phytophthora-infected trees, from completely asymptomatic ones, or from trees as above subjected also to treatments with amino acids (Amino16®) under different fertilization regimes. The interactions of bacterial communities with plant pathogenic oomycetes are crucial to determine the course of infection and the pathogenicity encompassing various functional contexts like biofilm formation. Thus, for deciphering the structure and diversity of these soil bacterial communities, we applied a 16S rRNA Illumina sequencing approach targeting the V3-V4 gene region. After quality check 478,479 sequences were obtained in the dataset comprising a total read length of 192,291,625 base pairs. Proteobacteria were the dominant phylum (46.1%) followed by Acidobacteria (13.2%) and Actinobacteria (12.4%). Different distributions of phyla were observed among our samples which is indicative of various alterations of soil bacterial communities in rhizosphere. The metagenome data from this survey are available at NCBI Sequence Read Archive (SRA) database and Biosample under accession number PRJNA542725.